2017
DOI: 10.1299/jamdsm.2017jamdsm0056
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic simulation of seat suspension system with virtual prototyping technology

Abstract: This paper will describe and simulate the dynamic response of an innovative suspension system for vehicle seat. In which, the isolated object is supported by a wedge mechanism which comprises a horizontal spring, a roller and a wedge. Besides, the dynamic stiffness of system is corrected by an auxiliary mechanism (AM) including a roller (follower) which always contacts the circular surface of the cam via another horizontal spring. Hence, this seat suspension prototype not only broad the excitation frequency re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…with θ(s) = µ 1 (s) + 2µ 2 (s) + 3µ 3 (s) Equation ( 30) revealed that sθ(s) > 0. By replacing u hit in Equation ( 17) by Equation ( 30), time derivation of the sliding surface is rewritten as shown in Equation (31).…”
Section:  mentioning
confidence: 99%
See 1 more Smart Citation
“…with θ(s) = µ 1 (s) + 2µ 2 (s) + 3µ 3 (s) Equation ( 30) revealed that sθ(s) > 0. By replacing u hit in Equation ( 17) by Equation ( 30), time derivation of the sliding surface is rewritten as shown in Equation (31).…”
Section:  mentioning
confidence: 99%
“…Furthermore, a fuzzy logic inference mechanism removes the chattering issue from conventional sliding mode control by employing a hitting control law. Currently, thanks to the robust development of engineering software, virtual prototyping technology can simulate and evaluate real system performance without experiments, lowering manufacturing costs and errors while ensuring product quality [30][31][32][33][34][35][36]. The tracking control performance of the EHA is evaluated through a virtual model created using Amesim software.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the efficiency of isolation of seat vibrations under low excitation frequencies, a model based on the philosophy of the previous QZS is proposed by Le and colleagues 16,25,26,37,38 (Figure 5). The main feature of this system is the use of two symmetric negative stiffness structures, consisting of one inclined bar ( b ) and one horizontal spring each ( K h ), coupled alongside a positive stiffness structure ( K v ).…”
Section: Simulation Modelsmentioning
confidence: 99%
“…NSS2 seat suspension model based on Le and colleagues. 16,25,26,37,38 at a random position x under the excitation z s .…”
Section: Simulation Modelsmentioning
confidence: 99%
“…The simulation results indicate that the proposed mechanism reduces the camber angle generation and decreases the camber thrust. The dynamic characteristics of seat suspension system were investigated by the method of virtual prototype by LE and Nguyen (2017). The results show that the model with an auxiliary mechanism outperforms the linear counterpart.…”
Section: Introductionmentioning
confidence: 99%